Tree biomass and carbon stock assessment of subtropical and temperate forests in the Central Himalaya, India - Vinod C. Joshi (Elsevier, 2021)
Forests are the world's largest carbon sink and play a vital role in climate change mitigation through carbon sequestration; thus the assessment of carbon stock in the forests is important for policy prescription and management planning. In view of this, present study is an attempt to assess the biomass and carbon stock of tree species in selected subtropical and temperate forest stands along the vertical elevation gradient (300 m to 2250 m) in the Central Himalaya. Volumetric equations (allometric method) were used for various tree species along with field sampling/ assessment (quadrat method) for biomass and carbon sequestration potentials. The total tree biomass and carbon stock of dominant forest stands varied from 227.23 to 577.16 Mg ha−1 (megagram per hectare), and 107.93 to 274.15 Mg C ha−1 respectively; it was found maximum for Sal (Shorea robusta) dominated forest and minimum for mixed Oak forest (Quercus floribunda, Q. lanuginosa, Q. leucotrichophora etc.). The carbon sequestration was recorded maximum (4.83 Mg C ha−1 yr−1) for Chir-pine stand (Pinus roxburghii) followed by Sal (4.63 Mg C ha−1 yr−1), mixed Oak (4.47 Mg C ha−1 yr−1), and minimum (3.99 Mg C ha−1 yr−1) for temperate Banj-oak forest (Quercus leucotrichophora). The contribution of above and below ground biomass among different forest stands was recorded 82% and 18% respectively. The dominant species contributed maximum biomass and carbon stock (70–82%) in pure Sal, Chir-pine and Banj-oak stand, while the contribution of dominant and co-dominant species in the mixed forest varied depending on forest composition. The results reveal higher carbon stock for subtropical forest as compared to temperate forest; however, it is interesting that there is no significant difference in carbon sequestration among the different forest stands. The study recommended for the assessing biomass and carbon stock of different forests for long-term management of forests and climate change mitigation.